Aplicación de contabilidad comercial en la empresa Lojanet Cia. Ltda. en la ciudad de Loja periodo: enero/2014 - Quezada Correa, Ana Cecilia (2015)
Today the importance of trade is reflected in the overall progress, as the free and fair trade is an essential tool for wealth creation and thus generating economic welfare of its people. The preparation of this work allowed the company LOJANET CIA LTDA., Have an information base commercial accounting system which permits the registration of economic movements according to International Accounting Standards to generate timely reports in decision making as manager of the production lines with higher returns, which will help the company with stronger projected forward in expendía computer products. In compliance with the objectives pose in the research project proceeded the inventory of the assets, rights and obligations available to the company at January 1, 2014 to then control the goods through the system of permanent account yielded information stocks Articles in the hold, starting with the implementation of the accounting process to the registration of the economic movements on the books until obtaining financial statements that will allow timely decision making. Finally it is concluded that the company was given the accounting according to the rules and principles of accounting in accordance with the request of the Superintendency of Company information that will be useful to prepare Financial Statements that are delivered to that entity